Advancing drug safety in psychiatry: insights from pharmacogenomics of hypersensitivity reactions - Alhaj, Hamid A.; Samara, Jana; Alnamous, Alyamama; Karima, Rama; Saber-Ayad, Maha (Frontiers in Pharmacology, 2025)
Drug hypersensitivity reactions (DHRs) to psychiatric medications represent a significant clinical challenge, often resulting in treatment discontinuation, poor adherence, and compromised patient outcomes. Pharmacogenomics has emerged as a promising field for understanding and mitigating these adverse effects by identifying genetic predispositions that affect drug metabolism, immune responses, and individual susceptibility. This narrative review explores the multifaceted mechanisms underlying DHRs, with a focus on immunological pathways, particularly T cell-mediated responses, drug metabolite formation, and genetic risk factors. Among these, human leukocyte antigen (HLA) alleles and polymorphisms in cytochrome P450 (CYP450) enzymes are critical contributors to hypersensitivity development. We provide a comprehensive analysis of pharmacogenomic associations with commonly prescribed psychiatric drugs, including anticonvulsants (e.g., carbamazepine, lamotrigine), selective serotonin reuptake inhibitors (SSRIs), and novel agents such as vortioxetine, psilocybin, and esketamine. Additionally, we examine antipsychotics, including clozapine and newer agents like aripiprazole, brexpiprazole, and cariprazine, highlighting specific gene-drug interactions and known risk alleles such as HLA-B*15:02, HLA-A*31:01, and variants in CYP2D6 and CYP1A2. These findings underscore the value of pharmacogenomic testing in predicting and preventing serious DHRs, such as Stevens-Johnson Syndrome, toxic epidermal necrolysis, agranulocytosis, and hepatotoxicity. The review also addresses clinical implementation, discussing the role of pre-emptive genetic screening, emerging guidelines from international consortia such as CPIC and DPWG, and real-world challenges, including variability in test accessibility, ethical concerns, and a lack of standardized protocols across regions. Recent advances in next-generation sequencing and multiomic approaches offer new opportunities to improve predictive accuracy and personalize psychiatric treatment further. Finally, we highlight the importance of population-specific research and global collaboration to close the evidence gap, particularly in underrepresented regions like the Middle East. This review emphasizes the transformative potential of pharmacogenomics in optimizing psychiatric drug therapy, enhancing safety, and ultimately improving patient-centered care.